Uniting Divided Worlds: Identity, Family and Education in the Life Projects of Deaf and Hard of Hearing Young People - Haualand, Hilde; Grnnings, Arne (Disability Studies Quarterly, 2003)
The article is based on a study of living conditions among Deaf and hard of hearing people 16 20 years old. Identification, family relations and education are discussed. This is the first generation of Norwegian Deaf and hard of hearing people whose parents have been offered real opportunity to learn sign language. Unlike earlier generations of sign language users, many of these youths have experienced personal as well as linguistic acceptance at home. They perceive themselves as obvious participators at a variety of local and global scenes and contexts both in hearing and Deaf worlds. They are uniting worlds that traditionally have been divided by language barriers. Among those who have not experienced the same degree of inclusion and acceptance as deaf or hard of hearing at home, questions of belonging to Deaf or hearing worlds seem to add pressure to the anxiety often connected to the teenage years.